Motor developmental delay in preschoolers with autism spectrum disorders in China and its association with core symptoms and maternal risk factors: a multi-center survey - Dan Long; Ting Yang; Jie Chen; Jie Zhang; Ying Dai; Li Chen; Feiyong Jia; Lijie Wu; Yan Hao; Ling Li; Xiaoyan Ke; Mingji Yi; et al. (Child and Adolescent Psychiatry and Mental Health)
Abstract Background Motor disturbance, as a related symptom of autism spectrum disorders (ASD), has not received the attention it deserves. We aimed to investigate the different degrees of motor developmental delay and influencing factors in Chinese preschool children with ASD, in order to enhance people’s awareness of motor developmental delay in ASD children. Methods We recruited 1,256 ASD children aged 2–6 years from the China Multi-Center Preschool Autism Project (CMPAP). We investigated the overall status of neurodevelopment in preschool children with ASD through the Revised Children Neuropsychological and Behavior Scale (CNBS-R2016) and the Gesell Developmental Scale (GDS). The multivariate ordered logistic regression model was used to analyze the relationship between different degrees of motor developmental delay and demographic, core symptoms of ASD, and maternal risk factors, which were evaluated using the questionnaires, the Childhood Autism Rating Scale (CARS) and the Social Responsiveness Scale-Second Edition (SRS-2). Results The proportions of delayed development in various neurodevelopmental domains was significantly imbalanced in preschool children with ASD. The proportions of gross and fine motor developmental delay were as high as 39.6% and 68.4% respectively. ASD children in different age subgroups all exhibited gross and fine motor developmental delay. The CARS and SRS-2 total scores of ASD children with mild, moderate-severe gross or fine motor developmental delay were significantly higher than those with normal motor skills development (P < 0.05). ASD children aged ≥ 5 years, or higher CARS and SRS-2 total scores, or gestational age in the 28–36+ 6 weeks were more likely to suffer from gross motor developmental delay (OR values were 5.504, 1.083, 1.846 respectively) and fine motor developmental delay (OR values were 2.216, 1.074, 1.011, 1.661 respectively). Conclusion Gross and fine motor developmental delay were difficulties that most preschool children with ASD may face, and ASD children with motor developmental delay had greater deficits in social skills. Therefore, it is necessary to continuously monitor the gross and fine motor development progress of children with ASD for facilitating early identification and individualized intervention.